Gamma Knife Radiosurgery for Tumors of the Endolymphatic Sac - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2015)
Tumors of the endolymphatic sac are locally invasive temporal bone neoplasms. Radical surgical excision is the treatment of choice; however, the aggressive nature of these tumors can make total excision impossible. Recurrence is common in cases of incomplete resection. Gamma knife radiosurgery was used to treat two patients with primary tumors of the endolymphatic sac and one recurrent case. All three patients were alive at 75, 74, and 11 months, respectively, after gamma-knife treatment, and the tumors were either smaller or had not enlarged. None of the patients experienced radiation-related side effects during follow up. Gamma knife radiosurgery should be considered a treatment option for these surgically challenging tumors.
Keywords: Endolymphatic sac tumor; Gamma knife; Radiosurgery; AGGRESSIVE PAPILLARY TUMOR; TEMPORAL BONE; FEATURES; CT